Mechanisms of SNR and line shape improvement by B0 correction in overdiscrete MRSI reconstruction. Issue 1 (10th February 2016) - Kirchner, Thomas; Fillmer, Ariane; Henning, Anke
Abstract : Purpose: Inhomogeneities of the main magnetic field cause line broadening and location‐dependent frequency shifts in brain MRSI. These are often visible despite advanced B 0 shimming. The purpose of this work is to propose an advanced B 0 correction method that can easily be applied during postprocessing. Methods: A target‐driven overdiscrete reconstruction method previously introduced for MRSI is modified by dividing it into two steps. In a first step, an intermediate spectroscopic image with arbitrarily high resolution is generated, on which B 0 correction is performed as an additional processing step based on an additionally acquired B 0 map. This frequency‐aligns metabolite peaks and destroys noise correlations between neighboring subvoxels. Second, the voxel is shaped by application of the spatial response target. The method was tested with simulated spectroscopic imaging data as well as in a series of MRSI data sets obtained from four healthy volunteers at 7T. Results: A systematic gain in spectral signal‐to‐noise ratio is achieved, due to spatial averaging now occurring over peak aligned and noise decorrelated subvoxel spectra. At the same time, metabolite peak line widths are reduced. Conclusion: In the presence of B 0 inhomogeneities across the field of view, the proposed method offers the potential to improve spectral quality with only a minimal additional effort during acquisition. Magn Reson Med 77:44–56, 2017. © 2015 Wiley Periodicals, Inc.